Model of the coil steels loading planning problem in railway carriage - D I Maftuhah; I Vanany; A R Muchsinin; D Rahadian (Institut Teknologi Sepuluh Nopember, 2018)
In this paper, the coil steels loading planning problem in trains is considered. This problem consists of determining the optimal assignment of coil steels to wagon slots of train in order to maximize the total weight of coil steels in railway carriage. Both knapsack problems and linear programming method are used to develop model of coil steels loading planning problem. The comparisons between the subjective adjustment method and the best solution of proposed model were conducted and were found through extensive experimental test of proposed model. The results of proposed model presented that the amount of coils steels that were more than and the weights of coil steels heavier than subjective adjustment method.